Peran Guru AUD Dalam Menstimulasi Perkembangan Bahasa Anak di TK Ikhlasul ‘Amal Medan - Siahaan, Hasnah; Muhammad, Arifin; Mahfudza, Amalia; Afni, Fitria Nurafni; Zr, Jamilah; Lestari, Sekar Ayu (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
This study aims to determine the role of the aud teacher in stimulating children's language development in Kindergarten Ikhlasul 'Amal Medan. In this study, the authors found that in Ra, the teacher's role in teaching focuses on children's